HIV-protease inhibitors block the replication of both vesicular stomatitis and influenza viruses at an early post-entry replication step - Federico, Maurizio (Virology, 2011)
The inhibitors of HIV-1 protease (PIs) have been designed to block the activity of the viral aspartyl-protease. However, it is now accepted that this family of inhibitors can also affect the activity of cell proteases. Since the replication of many virus species requires the activity of host cell proteases, investigating the effects of PIs on the life cycle of viruses other than HIV would be of interest. Here, the potent inhibition induced by saquinavir and nelfinavir on the replication of both vesicular stomatitis and influenza viruses is described. These are unrelated enveloped RNA viruses infecting target cells upon endocytosis and intracellular fusion. The PI-induced inhibition was apparently a consequence of a block at the level of the fusion between viral envelope and endosomal membranes. These findings would open the way towards the therapeutic use of PIs against enveloped RNA viruses other than HIV.